Analysis of Organizational Citizenship Behavior (OCB) on Employees at PT Perkebunan X - Gevio Kautsar; D A Wahab Sya’roni (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
An employee that are able to give more contribution beyond their regular organizational formal responsibilities is vital for the company’s productivity and competing in these volatile times. The purpose of this study is to understand how Organizational Citizenship Behavior (OCB) in the Perkebunan X company is perceived by both senior employees and also junior employees. The writer conducts this study by using a qualitative method in order to get a better understanding and the uniqueness from each of the subjects regarding the topics of this study by using five dimensions of OCB. Results found that there are differences between how senior and junior employees perceive OCB related to factors such as culture, compensation, age, and tenure